Adsorption of Chromium(VI) from Aqueous Solutions by Coffee Polyphenol-Formaldehyde/Acetaldehyde Resins. (26th December 2013) - Mulani, Khudbudin; Daniels, Siona; Rajdeo, Kishor; Tambe, Sanjeev; Chavan, Nayaku
Abstract : Removal of chromium(VI) from wastewater is essential as it is toxic. Thus, removal of chromium(VI) was performed using coffee polyphenol-formaldehyde/acetaldehyde resins as adsorbents. Adsorbent resins were prepared by condensation of decaffeinated coffee powder with formaldehyde/acetaldehyde and used for the removal of Cr(VI) ions from aqueous solutions. A simple and sensitive solid phase extraction procedure was applied for the determination of chromium at trace levels by spectroscopic method using 1, 5-diphenylcarbazide reagent. The adsorption of Cr(VI) on the coffee polyphenol-formaldehyde/acetaldehyde resins was monitored by FTIR and EDX analysis. The metal adsorption parameters such as contact time, pH, Cr(VI) ion concentration, and adsorbent dose were investigated. For Cr(VI), the maximum adsorption capacity of coffee polyphenol-formaldehyde resins was 98% at pH 2. The experimental results showed that Cr(VI) bound strongly with coffee polyphenol-formaldehyde/acetaldehyde resins and utilization of resins could be improved greatly by reuse.